PERAN PENDIDIKAN AGAMA ISLAM TERHADAP PEMBENTUKAN KEPRIBADIAN ANAK USIA DINI - Munawwarah Munawwarah; Loeziana Uce (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
The process of fostering religious values in shaping children's personalities can start from the time the child is born until he becomes an adult. When children are born they are introduced to the kalimah thoyyibah, then after they grow and develop into children, the first thing that must be instilled is religious values related to faith, so that children believe in the existence of Allah and can know Allah with certainty (ma' rifatullah). At the same time, children are also guided about moral values, such as how to speak well, dress well, socialize well, and so on. Good qualities are also instilled in children, such as the values of honesty, justice, simple living, patience and so on. This article uses a library research method. The purpose of this article is to describe the role of Islamic religious education in forming the character of early childhood. The research results show that Islamic religious education plays a role as the main foundation in forming the personality of early childhood. With the right approach, religious values can guide children to become individuals who are moral, have strong character, and are able to live life with good principles.